Evaluation of global Cenchrus germplasm for key nutritional and silage quality traits - Singh, Sultan; Singh, Tejveer; Singh, Krishan Kunwar; Srivastava, Manoj Kumar; Das, Madan Mohan; Mahanta, Sanat Kumar; Kumar, Neeraj; Katiyar, Rohit; Ghosh, Probir Kumar; Misra, Asim Kumar (Frontiers in Nutrition, 2023)
Cenchrus is important genera of grasses inhabiting tropical pastures and Indian grasslands system. Its forage value is well established to sustain nomadic livestock and wildlife. Study deals with the evaluation of the representative set of global Cenchrus collection with 79 accessions belonging to six species (C. ciliaris, C. setigerus, C. echinatus , C . myosuroides, C. pennisetiformis, C. biflorus) at flowering stage. Crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), cellulose and lignin values were in the range of 61.1-136, 640-749, 373-490, 277-375 and 35.6-75.50 g kg-1DM, respectively, while sugar contents varied from 11.6-101mg g-1 DM. From the evaluated germplasm 14 accessions of C ciliaris having >70 mg g-1 DM sugar contents were selected and further evaluated for protein, fiber, carbohydrate and protein fractions, palatability indices, in vitro CH4 production and ensiling traits. Protein contents were lower in EC397323 (61.8) and higher in IG96-96 (91.5), while the NDF, ADF, cellulose and lignin contents ranged between 678-783, 446-528, 331-405 and 39.6-62.0 g kg-1DM, respectively. The carbohydrate and protein fractions of selected accessions differed (P<0.05) with sugar contents varied (P<0.05) between 74.6-89.6 mg-1g DM. Dry matter intake (DMI) and relative feed value (RFV) of accessions varied (P<0.05) and were in the range of 1.53-1.77% and 58.2-73.8 g kg-1 DM, respectively. The total digestible nutrients (TDN), digestible energy (DE) and metabolisable energy (ME) of selected accessions varied between 362-487 g kg-1 DM, 6.62-8.90 and 5.42- 7.29 Mj kg-1 DM, respectively. In vitro gas and CH4 production (24h) varied (P<0.05) between 73.1 to 146 and 7.72 to 21.5 ml/g, respectively, while the degraded dry matter (DDM %) and CH4 (ml/g DDM) ranged between 399-579 and 17.4-47.2, respectively. The DM contents at ensiling, silage pH and lactic acid contents of accessions differed (P<0.05) and ranged between 185-345 g kg-1 DM, 5.10-6.05 and 1.39-23.3 g kg-1 DM, respectively. Wide genetic diversity existed in germplasm and selected C. ciliaris accessions for protein fiber, energy, sugar and other nutritional traits. Silage prepared from EC397366, IG96-96, IG96-50 and EC397323 had pH and lactic acid contents acceptable for moderate to good quality silage of tropical range grasses.